The urban and regional impacts of plant closures: new methods and perspectives. Issue 1 (1st January 2019) - Beer, Andrew; Weller, Sally; Barnes, Tom; Onur, Ilke; Ratcliffe, Julie; Bailey, David; Sotarauta, Markku
ABSTRACT: Work on large-scale plant closures has provided a rich vein of scholarship and academic debate. This paper articulates a new set of methods and concepts for understanding how large-scale redundancies associated with the closure of manufacturing plants affects society and the economy at the local, regional and national scales. It posits the need for a more comprehensive exercise in data collection and experimentation with previously unused methods, including the application of discrete-choice experiments in order to understand better the choice and decision-making frameworks adopted by affected workers. The paper argues there is a need to integrate community-wide policy responses into the core of the analyses.